Diversity and traditional ethnozoological uses of ichthyofauna by the Bodo Tribes of Kokrajhar, Assam, Northeast India - GANDOLI BASUMATARY; BICHITRA NARZARY; BRONSON KUMAR KHANGEMBAM (Nusantara Bioscience, 2023)
Abstract. Basumatary G, Narzary B, Khangembam BK. 2023. Diversity and traditional ethnozoological uses of ichthyofauna by the Bodo Tribes of Kokrajhar, Assam, Northeast India. Nusantara Bioscience 15: 49-57. Fish is an important component of ethnomedicine for treating many diseases in many tribal cultures worldwide. Traditional medicine remains the primary healthcare system in most rural populations worldwide, and ethnomedicine is the foundation of many modern-day disease management. The use of fish in traditional healthcare could be a potent source for finding new compounds with therapeutic prospects. Studies on ethnoichthyology have indicated fish as an important component for treating many diseases. However, such studies are yet to be fully documented in the northeastern states of India, especially in Kokrajhar, Assam. The Bodos are one of the largest tribal groups of Assam in Northeast India, with a rich traditional knowledge system. The study explores the traditional uses of fish for various ethnomedicinal properties and health benefits by the Bodos of Kokrajhar, Assam. The study was conducted in eight villages of Kokrajhar District from March 2019 to February 2020 through personal interviews and semi-structured questionnaires with 150 informants. Thirty-four different fish species from 20 different families were identified to be used for their health benefits and therapeutic properties. The highest number of fish species belonged to the family Cyprinidae (20.59%), followed by Channidae (11.76%) and Ambassidae (8.82%). The highest use value (0.58) and relative frequency of citation (0.37) was recorded for Heteropneustes fossilis. Anaemia, gastrointestinal and integumentary disorders, and body weakness were the most commonly mentioned ailments treated. The present study also reported some small indigenous fish species for their health benefits. The study also found some unique traditional methods for preparing and applying fish species (Xenentodon cancila, Chitala chitala, Glossogobius giuris, Leiodon cutcutia, etc.) not reported earlier. Identification and detailed study of the biochemical profile of these different species may be recommended to develop suitable alternatives to synthetic medicines. This study may be a valuable addition to the rich traditional knowledge of Northeast India.